The roles and functions of PRN - Abd Razak, Dzulkifli (1995)
With the rise of number of poisonings as a result of new developments in industrial chemicals, there was an urgent need for toxicology to direct itself to the issue at hand. One such response is an establishment of a specialized centre where the reports on cases of poisoning from all sources could be centrally handled. At the same time such centre could provide assistance with respect to treatment as well as prevention where information seems to be the stumbling block especially in emergency cases. Such centres eventually come to be known as Poison Control Centres, or simply Poison Centres. The first Poison Centre was set up in 1949 in Holland, Europe acting mainly as information centre. At that time its sole function is to provide complete information about drugs and medicinal plants, indicating toxicity, contraindications, and what to do in cases of poisoning.